1998
DOI: 10.1089/dna.1998.17.161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Chromosomal Localization, and Expression Analysis ofCYRN1andCYRN2, Two Human Genes Coding for Cyritestin, a Sperm Protein Involved in Gamete Interaction

Abstract: Germ cell cyritestin is a membrane-anchored protein belonging to the ADAM family of proteins. Sequencing of eight human cyritestin cDNA clones revealed that they are identical at their 5' and 3' ends but differ from each other in the length of an internal deletion, suggesting that the human cyritestin mRNA is alternatively spliced. Internal deletions that are present in some cDNA isoforms do not cause a frameshift in the C-terminal coding region. Analysis of the predicted amino acid sequences demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Recently, Adham and co-workers [17] have reported sequences for four human tMDC I transcripts (which they call CYRN1), which all contain the same 83 bp deletion that we observe ( Figure 1, Deletion I ) at the beginning of the coding region. However, all four CYRN1 transcripts apparently lack the 1 bp deletion (Figure 1, Deletion II ) and the second in-frame termination codon within the metalloproteinase-like domain (Figure 1, Stop II) and contain an additional deletion of 2 bp within the region encoding the putative signal peptide.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Recently, Adham and co-workers [17] have reported sequences for four human tMDC I transcripts (which they call CYRN1), which all contain the same 83 bp deletion that we observe ( Figure 1, Deletion I ) at the beginning of the coding region. However, all four CYRN1 transcripts apparently lack the 1 bp deletion (Figure 1, Deletion II ) and the second in-frame termination codon within the metalloproteinase-like domain (Figure 1, Stop II) and contain an additional deletion of 2 bp within the region encoding the putative signal peptide.…”
Section: Discussionsupporting
confidence: 77%
“…This 2 bp deletion, as well as the absence of the 1 bp Deletion II (see Figure 1) are not observed in any of the independent clones, isolated from many individuals, which we report here. In addition, two of the four CYRN1 cDNA clones and four out of four characterized CYRN1 PCR products (also described by Adham et al [17]), all contained deletions or insertions associated with the disintegrin-like domain, the region implicated in egg binding.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the sperm of the cyritestin null male mouse is incapable of binding to the ZP. Interestingly, several researchers have reported that there are two human cyritestin genes, CYRN1 and CYRN2, localized on chromosomes 8p12-21 and 16q12, respectively [18]. Evidence suggests that human cyritestin genes are non-functional, as judged by Western blot analysis using rabbit antisera against human and macaque CYRN1 and the presence of a variety of deletions, insertions and premature termination in humans [19].…”
mentioning
confidence: 99%